Strategi Pembelajaran Kooperatif Tipe Jigsaw Versus Pembelajaran Langsung - Mashudi Mashudi (IAIN Kediri, 2016)
One of problem that needs attention in learning activity is learning method, technique, and strategy. Cooperative learning strategy has some elements namely (1) positive inter-dependency, (2) face-to-face, (3) individual responsibility, (4) group and interpersonal skill, and (5) group process effectiveness. The theory basis of cooperative learning comes from different perspective. This article elaborates cooperative learning with behaviorism and constructivism theories, especially cooperative learning Jigsaw type. As Slavin stated that the techniques that use the appropriate approach are Jigsaw, Group investigation, and Learning Together. The advantages of cooperative learning are (1) increasing positive attitude toward learning activity, (2) rousing interaction among students, (3) increasing learning achievement, and (4) authentic assessment.